Gravitational and oceanographic processes interaction in the upper slope gullies of the Gulf of Cadiz - García, Marga; Mena, Anxo; Hernández-Molina, Francisco J.; Alonso, Belén; Ercilla, Gemma; Casas, David; Llave, Estefanía; Fernández-Salas, L. M.; Lobo, F. J. (Sociedad Geológica de España, 2021)
X Congreso Geológico de España, 5-7 de julio 2021, Vitoria-Gasteiz.-- 4 pages, 4 figures [EN] The Gulf of Cadiz upper slope in the area close to the Strait of Gibraltar is covered by a plastered drift deposited by the activity of the Mediterranean Outflow Water (MOW) and the North Atlantic Central Water (NACW). A number of small gullies are incised across the plastered drift, due to the interaction between gravitational and contouritic processes. The study of parametric sounder profiles and sedimentological analyses of nine sediment cores obtained from the axes of two gullies and from the undisturbed upper slope, giving a Holocene age frame, has allowed analyzing the recent sedimentary processes and their spatial and temporal variability. The upper slope shows a general increase in grain size towards the NW, suggesting bottom current intensification and/or the occurrence of gravity flows from the continental shelf and shelf-edge. The two studied upper slope gullies display significant differences in their recent activity and dominant processes. The one located to the SE seems to have been inactive since about 5.9 ka, and it has been draped by contouritic deposits. In contrast, the gully located to the NW has been a sediment transport conduit for the entire time span recorded in the sediment cores [ES] El talud superior del margen Ibérico del Golfo de Cádiz en las proximidades del Estrecho de Gibraltar está ocupado por un depósito contornítico adosado resultado de la circulación del Agua Mediterránea de Salida (Mediterranean Outflow Water, MOW) y de la Masa de Agua Central Noratlántica (North Atlantic Central Water, NACW). En él se encajan pequeños valles submarinos (gullies) debido a la interacción entre los procesos gravitacionales y contorníticos. Mediante el estudio de perfiles de sonda paramétrica y el análisis sedimentológico de nueve testigos obtenidos en el área del talud superior no afectada por gullies y en los ejes de dos gullies, cuya datación corresponde al Holoceno, este estudio analiza los ...